1986
DOI: 10.1002/art.1780290402
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 lymphocyte chemotactic activity in rheumatoid arthritis synovial fluid

Abstract: We examined the role of interleukin-1 (IL-1) in the chemotactic activity of rheumatoid arthritis (RA) synovial fluid (SF). Crude RA SF was found to be chemotactic for B cells and T cells. After AcA 54 gel filtration, the principal peaks of chemotactic activity were found in the 5-kd, 16-kd, and 60-kd fractions. The majlority of the chemotactic activity for both the B cells (74-85%) and the T cells (69-78%) was removed from these fractions by treatment with anti-IL-1 antibody. However, in crude SF, approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…The striking serum dependence of colony growth for synoviocytes from both rat and human arthritic joints and the known presence of certain cytokines in serum and rheumatoid synovial fluid led us to examine the effects of various cytokines on the anchorage-independent growth. Previous work has demonstrated PDGF, EGF, and insulinlike growth factors in serum (16,17), and rheumatoid synovial fluids are known to contain IL-i (18,19), TNF-alpha (20), IFN-gamma (21, 22), EGF (23), PDGF, and TGF-beta (24). Therefore, the effects of these cytokines on anchorage-independent synoviocyte growth were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The striking serum dependence of colony growth for synoviocytes from both rat and human arthritic joints and the known presence of certain cytokines in serum and rheumatoid synovial fluid led us to examine the effects of various cytokines on the anchorage-independent growth. Previous work has demonstrated PDGF, EGF, and insulinlike growth factors in serum (16,17), and rheumatoid synovial fluids are known to contain IL-i (18,19), TNF-alpha (20), IFN-gamma (21, 22), EGF (23), PDGF, and TGF-beta (24). Therefore, the effects of these cytokines on anchorage-independent synoviocyte growth were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the previously demonstrated matrix-synthesizing capabilities of the human synovial fibroblast, we hypothesized that this cell may be a rich source of type VI collagen in synovium. Interleukin-I (IL-l), a cytokine whose presence in synovial fluid and synovial tissues in a variety of arthropathies is well documented (13), is known to influence a number of articular cell functions. IL-1, for example, is not only a potent stimulus for the synthesis and release of prostaglandins and proteases from synovial fibroblasts and chondrocytes (3,4), but it also appears to play a role in regulating the synthesis of fibrillar collagens by these cells (14,15).…”
mentioning
confidence: 99%
“…Among these alterations are changes in hepatic synthesis of a number of plasma proteins, referred to as acute-phase proteins; synthesis of some proteins, the positive acute-phase proteins, increases, while synthesis of others, the negative acute-phase proteins, decreases. Studies in primary hepatocyte cultures and hepatoma cell lines have shown that hepatic synthesis of human acute-phase proteins can be influenced by several cytokines including interleukin 6 (IL-6), a major inducer ofacute-phase changes, interleukins la and -p8 (IL-1), cachectin/tumor necrosis factor a (TNF), interferon y, and leukemia inhibitory factor (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). One cytokine can modulate the effect of other cytokines in human model systems-e.g., IL-1 diminishes the inducing effect of IL-6 on fibrinogen synthesis (7,12,18) and interferon y…”
mentioning
confidence: 99%